2018
DOI: 10.1115/1.4041854
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Numerical Simulation of the Structural Performance of Fused Deposition Modeling Samples With Variable Infill Values

Abstract: The prediction of the structural performance of additive manufacturing (AM) parts has become one of the main challenges to boost the use of AM in industry. The structural properties of AM are very important in order to design and fabricate parts not only of any geometrical shape but also with variable or customized mechanical properties. While AM experimental studies are common in the literature, a limited number of investigations have focused on the analysis and prediction of the mechanical properties of AM p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Simulation models and multi-objective optimization methods were also used to analyze the effects of process parameters on the selected response variables. [89][90][91][92][93] Mercedes et al [94] investigated and identified the essential factors that influence the surface integrity of fused filament fabricated PLA samples. They experimented with five printing factors, including layer height, printing speed, temperature, wall thickness, and printing path, to determine the ideal combination of these to reduce the printed part's surface roughness.…”
Section: Environmental Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Simulation models and multi-objective optimization methods were also used to analyze the effects of process parameters on the selected response variables. [89][90][91][92][93] Mercedes et al [94] investigated and identified the essential factors that influence the surface integrity of fused filament fabricated PLA samples. They experimented with five printing factors, including layer height, printing speed, temperature, wall thickness, and printing path, to determine the ideal combination of these to reduce the printed part's surface roughness.…”
Section: Environmental Temperaturementioning
confidence: 99%
“…Simulation models and multi‐objective optimization methods were also used to analyze the effects of process parameters on the selected response variables. [ 89–93 ]…”
Section: Pre‐processing Techniquesmentioning
confidence: 99%
“…Numerous papers that elucidate simulation tests utilizing the finite element method fail to establish a comparison between outcomes attained through experimental tests. This includes papers that exclusively employ mechanical parameters of the material [ 24 , 25 , 26 , 27 ] and those that solely delineate the technique for applying loads to a simulated model of the orthosis [ 28 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are many articles describing simulation tests using the finite element method in which the results obtained were not compared with experimental tests. Some examples, where the mechanical parameters of pure material were adopted can be found in [ 19 , 20 , 21 , 22 ]; another example, where only the method of loading the orthosis simulation model is described, can be found in [ 23 ].…”
Section: Introductionmentioning
confidence: 99%